The Brexit Hammer: Repercussions for the US and Transatlantic Relations in Times of Corona - KOHNERT, Dirk (Theoretical and Practical Research in Economic Fields, 2021)
The global revival of economic nationalism and protectionism poses a serious threat to the international foreign trade policy orientation towards principles of a market economy. Popular economic nationalism such as Trumpism, Brexit or the isolation of the Eastern European Visegrád states from immigrants violates fundamental principles of the WTO. Economists agree that Brexit will hurt the UK economy significantly in the medium and long term. In addition, its political and economic effects will damage the US and transatlantic relations. British Prime Minister Boris Johnson, on the other hand, continues to claim that leaving the EU will enable Britain to "take back control". In addition, the socio-economic effects of the Corona crisis on the US, UK, EU and transatlantic relations are devastating. It has far-reaching political, social and economic consequences that go well beyond public health. All partners need each other more than ever to cope with the Covid crisis. Increased transatlantic cooperation to strengthen resilience would also be necessary in closely related areas of international relations and security issues.